Activation of Zr, ZrVHf and TiZrV Non-Evaporative Getters Characterized by In Situ Synchrotron Radiation Photoemission Spectroscopy - Yuchen Yang; Yongsheng Ma; Jia’ou Wang; Tao Huang; Baiqi Liu; Fei Sun; Xujian Wang; Shuangkai Chen; Zilin Chen; Xiaohua Peng; Haiyi Dong; Ping He (Applied Sciences, 2021)
The activation process of Zr, ZrVHf and TiZrV non-evaporative getter (NEG) thin films, prepared by direct current magnetron sputtering, is investigated by in situ synchrotron radiation photoemission spectroscopy. The activation temperatures of Zr and ZrVHf films are found to be 300 °C and 200 °C, respectively, and the activation temperature of TiZrV film is 120 °C—the lowest activation temperature reported on TiZrV. As the heating temperature increases, the transformation of metal-C bond follows the orders of V–C, Ti–C, Zr–C, Hf–C. It is found that the order of reduction difficulty of the same element oxides, that is, Zr oxide and V oxide in different films follows Zr film > ZrVHf film > TiZrV film. The order of difficulty in the reduction of oxides in the same alloy NEG films follows HfO2 > ZrO2 > TiO2 > V2O5. We propose that the above phenomena can be explained by interstitial diffusion, grain boundary diffusion of residual gas atoms and grain boundary precipitation of V and Ti in the solid solution of the NEG films.